2018
DOI: 10.1007/s10096-018-3244-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of carbapenem-resistant Pseudomonas aeruginosa in an endemic area: comparison with global data

Abstract: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is an endemic problem in certain countries including Greece. CRPA and multidrug-resistant P. aeruginosa (MDRPA) firstly emerged in our region during the 80s, right after the launch of imipenem and meropenem as therapeutic agents against P. aeruginosa infections. The role of outer membrane protein (Opr) inactivation has been known to contribute to imipenem resistance since many years, while efflux overexpression systems have been mainly associated with meropene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 108 publications
1
29
0
Order By: Relevance
“…Emergence and rapid dissemination of carbapenem resistance among P. aeruginosa and A. baumannii is considered to be one of the most serious global health issues (WHO ) . To date, most of the studies have demonstrated pivotal role of bla VIM and bla OXA in conferring carbapenem resistance among pathogenic P. aeruginosa and A. baumannii respectively (Karampatakis et al ; Karampatakis et al ). However, in Indian scenario, contribution of bla NDM in carbapenem resistance development cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergence and rapid dissemination of carbapenem resistance among P. aeruginosa and A. baumannii is considered to be one of the most serious global health issues (WHO ) . To date, most of the studies have demonstrated pivotal role of bla VIM and bla OXA in conferring carbapenem resistance among pathogenic P. aeruginosa and A. baumannii respectively (Karampatakis et al ; Karampatakis et al ). However, in Indian scenario, contribution of bla NDM in carbapenem resistance development cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…). To date, most of the studies have demonstrated pivotal role of bla VIM and bla OXA in conferring carbapenem resistance among pathogenic P. aeruginosa and A. baumannii respectively(Karampatakis et al 2017;Karampatakis et al 2018). However, in Indian scenario, contribution of bla NDM in carbapenem resistance development cannot be overlooked.…”
mentioning
confidence: 99%
“…For example, IMP-6, which has only one amino acid substitution (serine to glycine at position 214) from IMP-1 (Additional file 6: Figure S6), enhanced the resistance to meropenem, and meropenemresistant Enterobacteriaceae, K. pneumoniae, and P. aeruginosa carrying blaIMP-6 have been spreading in Japan since 2001 [67,68]. Similarly, VIM-4, which has only one amino acid insertion (arginine at position 44) and one amino acid substitution (serine to arginine at position 265) from VIM-1 (Additional file 7: Figure S7), enhanced the resistance to carbapemems, and P. aeruginosa carrying blaVIM-4, which was first reported in 2002, has already been detected worldwide [69,70]. IMP and VIM are mainly included in the integron structure and are integrated into chromosomal DNA and plasmid DNA in association with the transposon [60,65].…”
Section: Class B Mblmentioning
confidence: 99%
“…β-lactamases from all four Ambler classes have been described in P. aeruginosa, including Class A extended spectrum β-lactamases (ESBLs) of the TEM, SHV, CTX-M, GES, PER and VEB types; Class A carbapenemases such as KPC variants; metallo-β-lactamases such as the VIM, IMP, NDM and SPM B1 di-Zn 2+ enzymes: and OXA carbapenemases [9,12]. Weak imipenemases in the so-called Class C AmpCs have already been discussed above.…”
Section: Acquired β-Lactamases In P Aeruginosamentioning
confidence: 99%